Feasibility of a Millimeter-Wave MIMO System for Short-Range Wireless Communications in an Underground Gold Mine - Ben Mabrouk, Ismail; Hautcoeur, Julien; Talbi, Larbi; Nedil, Mourad; Hettak, Khelifa (IEEE Transactions on Antennas and Propagation, 2013)
The performance of multiple-input-multiple-output (MIMO) system operating at the 60 GHz band is investigated based on experimental data in a real underground mine gallery. However, the millimeter wave (mmW) channels face some challenges such as high propagation loss. In order to overcome this issue, a planar microstrip antenna array has been designed, and fabricated. Moreover, the effect of miners' activity in the vicinity of the short-range wireless link is studied. Statistical parameters of the propagation channel, such as RMS delay spread, path loss, K-factor, channel correlation and capacity are extracted and analyzed. Results suggest that miners presence substantially affects both received power and time dispersion parameters and should therefore be considered when developing underground mine wireless networks in the unlicensed 60-GHz band.